PENGARUH PHYGITAL CUSTOMER EXPERIENCE, DIGITAL GREEN TRANSPARENCY, DAN CARBON FOOTPRINT INFORMATIONTERHADAP ONLINE PURCHASE DECISIONPRODUK ECO-FRIENDLY HOUSEHOLDPADA GENERASI Z DENGAN ENVIRONMENTAL CONCERNSEBAGAI VARIABEL MODERASI - Hera Glenis Neysa; Ratri Nurina Widyanti (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study examines the effects of phygital customer experience, digital green transparency, and carbon footprint information on the online purchase decision of eco-friendly household products among Generation Z, with environmental concern as a moderating variable. A quantitative survey was conducted involving 150 Generation Z respondents in Indonesia who had purchased environmentally friendly household products through e-commerce platforms. Data were collected using an online questionnaire and analyzed with SEM-PLS. The results reveal that phygital customer experience, digital green transparen cy, and carbon footprint information positively and significantly influence online purchase decisions, Environmental concern stren gthens the relationships between these variables and purchase decisions. The findings suggest that businesses should enhance dig ital marketing strategies by providing transparent environmental information and educating consumers about product carbon footprints to encourage sustainable online purchasing behavior.